TARAS SHEVCHENKO’S VISUAL IMAGE: THE ANTHROPOLOGIST’S NOTES - Сегеда, С. Т. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article examines anthropological peculiarities of Taras Shevchenko’s personality throughout all of his life. Using biographical moments from the poet’s creations, the author “depicts” Kobzar’s appearance and posture, which underwent changed due to social and physical factors.